Hexagonal and rhombohedral polytypes in indium selenide films grown on c-plane sapphire - L. de Brucker; M. Moret; B. Gil; W. Desrat (AIP Advances, 2022)
We report on the growth of 2D layered indium selenide films on (0001)-oriented sapphire substrates by coevaporation. The θ − 2θ x-ray diffractograms reveal that the (00l) planes are preferentially oriented parallel to the substrate with a tendency to deviate from the 2D stacking as a function of the growth time. The ϕ-scans performed for the (107) and (10 10) orientations of the hexagonal (h) and rhombohedral (r) phases, respectively, reveal that both polytypes coexist in the epitaxial films. We show that the merging of the h-(100), r-(101), h-(101), and r-(102) lines results in different spectral shapes in the θ − 2θ scans according to samples, which gives qualitative information about the contribution of each polytype.